Effects of diet on skin sensitization by nickel, poison ivy, and sesquiterpene lactones. (March 2020) - An, Nan; Pourzal, Selma; Luccioli, Stefano; Vukmanović, Stanislav
Abstract: Skin contact or exposure to sensitizers often occurs as a consequence of occupational exposures (e.g. poison ivy in forestry), wearing jewelry (e.g. nickel), or use of cosmetics (e.g. fragrances). However, many of the known skin sensitizers or their chemical variants are also consumed orally through foods or other sources. Since oral exposure to antigenic substances can lead to tolerance, consumption of sensitizers may impact the development and potency of skin sensitization, especially if the sensitizer is consumed early in life, prior to the first skin contact. To address this issue, we have reviewed human clinical and epidemiological literature relevant to this subject and evaluated whether early oral exposures to relevant sensitizers, or their chemical variants, are associated with reduced prevalence of skin sensitization to three main allergic sensitizers – nickel, urushiols of poison ivy, and sesquiterpene lactones of chrysanthemum and other plants. Highlights: Many skin sensitizers are consumed orally through foods or other sources. Specific antigen tolerance can be induced through early oral exposure to antigen. Developmental tolerance to nickel, urushiol and sesquiterpene lactones was explored. Associations are established between early exposure and reduced sensitization rates. Controlled studies with specific sensitizer early life exposure are needed.